Interpersonal relationships management potentials for the engineering students’ development - Castillo Elizondo , Jaime Arturo; Treviño Cubero , Arnulfo; Banda Muñoz , Fernando; Cúpich Guerrero , Jorge Alejandro (Transformación, 2024)
This article is aimed at supporting the importance of the process of social relations in the engineer student training process and highly its educative potentials by means of historical analysis of its evolution. It´s obvious that talking about this subject raises a very wide and complex topic for discussion, but the paper shows you few of the results of the first stage of a research made at the Autonomous University of Nuevo León, Mexico. It shows us the results at the exploratory stage of the research; the purpose of the evolution of social relationship, as well as the description of some scores obtained through the survey techniques, that help us to identify its mainly achievements as well as its limitations.
Keywords: social relations; interpersonal relationships management; university training